2002
DOI: 10.1093/jpepsy/27.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Children's Response to an Invasive Medical Investigation: The Influence of Effortful Control and Parent Behavior

Abstract: Factors relating to the child (effortful control) and parent (coping and distress-promoting behaviors) both contribute to children's response to an aversive medical procedure. Interventions that facilitate parent coping and promoting behavior, reduce their distress-promoting behavior, and compensate for children's infrequent and ineffective use of coping strategies (such as distraction) may be optimal for young children, particularly those low in effortful control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 19 publications
4
46
0
2
Order By: Relevance
“…Other parents, in their attempts to manage their child's (and perhaps their own) distress, inadvertently denied or minimized the child's experience with statements such as, "It's not so bad," or "It doesn't really hurt," which seemed to infuriate some children into more vigorous vocalizations of their plight and exacerbate their distress overall. This observation is consistent with other studies (eg, 5 ) that have found parental reassurance and other "distress-promoting" behaviors such as criticism, empathic comments, and apology to be among the strongest predictors of child distress during the procedure.…”
Section: Clinical Observations To Inform Research and Practicesupporting
confidence: 92%
See 1 more Smart Citation
“…Other parents, in their attempts to manage their child's (and perhaps their own) distress, inadvertently denied or minimized the child's experience with statements such as, "It's not so bad," or "It doesn't really hurt," which seemed to infuriate some children into more vigorous vocalizations of their plight and exacerbate their distress overall. This observation is consistent with other studies (eg, 5 ) that have found parental reassurance and other "distress-promoting" behaviors such as criticism, empathic comments, and apology to be among the strongest predictors of child distress during the procedure.…”
Section: Clinical Observations To Inform Research and Practicesupporting
confidence: 92%
“…The entire experience and the urethral catheterization in particular can be painful, frightening, embarrassing, and even traumatic. 5,6 In addition, because of the proximity of the urethra to other genital structures and perhaps because of concerns of future sexuality-associated memory, parents find this procedure particularly anxiety provoking. As a result, the procedure is often a difficult and stressful experience for parents and medical personnel as well.…”
mentioning
confidence: 99%
“…This adds to discussions identified in earlier studies on restraint (Brenner et al, 2014; Kangasniemi et al, 2014; Kirwan & Coyne, 2016), where studies on distress and pain have found that what parents say and do clearly affect children’s ability to cope with the procedure (Salmon, 2006; Salmon & Pereira, 2002). McCarthy et al (2010) investigated factors affecting children’s responses to PVC and concluded that parental expectations of distress and distractive communication influenced the children’s level of distress.…”
Section: Discussionsupporting
confidence: 53%
“…Self-regulation is associated with decreased fear, positive affect, and reduced frustration levels in young children 51,54 and with effective coping during medical procedures. 55 Further work on the interaction of child temperament and coping offers much promise for guiding the development of individualized preprocedure preparation interventions.…”
Section: Temperament and Coping Stylementioning
confidence: 99%
“…Conversely, parental criticism, anxiety, and excessive verbal reassurance can increase children's stress. 55,57,59,60 Interventions aimed at addressing parental concerns regarding children's hospitalizations have been effective in decreasing parental anxiety and enhancing child behavioral outcomes. 8,50 Active parental participation in the preprocedure process also enhances the efficacy of a variety of preprocedure preparation methods, including preprocedure class, peermodeling videotapes, or brief explanations by nurses.…”
Section: Role Of Parentsmentioning
confidence: 99%